Capitalism, sport mega events and the global south - Graeff, Billy (Abingdon, Oxon ; New York : Routledge, 2020)
"What are the social, political and economic consequences of staging sport mega events such as the Olympics and the World Cup? Capitalism, Sport Mega Events and the Global South presents a new approach to sport mega events and related issues, exploring elements that are not present or are not developed in the existing literature. This book explores the socioeconomic impact of these events on host countries in the Global South. Drawing on a thorough case study of the 2014 FIFA World Cup in Brazil, it examines how the residents of Porto Alegre perceived how they were affected and considers the relationship between sport mega events and the wider social sphere of global capitalism. Supported by original socioeconomic research conducted in the area, this is fascinating reading for all students and scholars interested in sport mega events, sport tourism, international development, sport geography, and the sociology of sport"--
Introduction -- Global capitalism and sport mega events -- Sport mega events: discourse x practice -- The socioeconomic consequences of the sport mega events 'tour' through the Global South -- Local impacts of global events: Porto Alegre and the 2014 World Cup -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Hosting of sporting events -- Economic aspects -- Developing countries; Hosting of sporting events -- Social aspects -- Developing countries; Professional sports -- Economic aspects -- Developing countries; SPORTS & RECREATION / General; SPORTS & RECREATION / Sociology of Sports